The need for emergency treatment of transient ischemic attack and minor stroke. - Giles, M; Rothwell, P (2005)
The risk of recurrent stroke following transient ischemic attack or minor stroke has recently been shown to be 5-10% at 1 week and 10-20% at 3 months, depending on study population and methods. This is considerably higher than previously estimated and current clinical guidelines reflect the need for rapid assessment although a wide variation in practice exists. Effective management of patients with transient ischemic attack or minor stroke, therefore, requires identification of individuals at the highest (and lowest) risk and initiation of appropriate secondary prevention. Risk can be stratified at initial presentation by the presence or absence of simple clinical features and following subsequent investigation. For transient ischemic attack patients, older age, diabetes, longer duration of symptoms and weakness or speech disturbance identify patients at highest risk, as does the presence of large artery atherosclerosis (mainly internal carotid artery stenosis) and lesions on diffusion-weighted magnetic resonance imaging. Strong evidence exists for the benefit of some early interventions (carotid endarterectomy and antiplatelet agents), but is circumstantial or awaited for others (statins and antihypertensives). In order for the public health challenge posed by transient ischemic attack and minor stroke to be met, considerable change is required in both public education (to ensure correct recognition of symptoms and swift presentation to medical attention) and the provision of clinical services to ensure the timely initiation of effective treatment.